Papers - Refining - Fire Refining - A Comparison of Use of Various Fuels in Copper-refining Furnaces (With Discussion) - E. S. Bardwell (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1934)
The reverberatory copper-refining furnaces at the Great Falls Reduction Dept. of the Anaconda Copper Mining Co. have used successively as fuel, lump coal on grates, pulverized coal, oil and natural gas. In no other plant, so far as can be ascertained, has such a variety of fuels been used. This fact affords a unique opportunity for comparing the relative efficiency obtained with these several fuels under nearly identical conditions. Furnaces The present furnace refinery at Great Falls was placed in operation in April, 1916. The original installation consisted of two furnaces, each with hearths 36 by 14 ft. and provided with fireboxes 10 by 12 ft. for firing lump coal on grates. These furnaces had air-cooled sand bottoms and chrome-brick side walls both above and below the metal line. The roofs were of 12-in. silica brick. Each furnace was provided with a waste-heat boiler of approximately 400 boiler-hp. capacity. We soon found that chrome brick was very unsatisfactory as side-wall material because of its excessive spalling. At the first opportunity the furnaces were rebuilt, using magnesite brick below the metal line and silica brick from the metal line to the roof. At the same time the thickness of the side walls was increased, thus decreasing the width of the hearth to 13 ft. At about this time also, the thickness of the furnace roofs was increased from 12 to 15 in. No further changes occurred in furnace design until 1922, when the use of lump coal on grates was abandoned in favor of pulverized coal. The first charge to be melted and refined with pulverized coal was cast on March 30, 1922. When pulverized coal first was used the burner pipes were introduced directly into the firebox as it was felt that some kind of a combustion chamber might prove necessary, but this was not needed. The fireboxes were dismantled and the burners introduced through openings directly over the bridge wall. During the summer of 1922 one of the furnaces was completely rebuilt, lengthened 10 ft. and provided with a silica-brick bottom in the form of an inverted arch. At